Les insectes dans les collections patrimoniales – Du naturel au pathologique - Grazia Nicosia (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The rhetorical presentation of  insects, considered as a pest or a cultural heritage allows us to recontextualize the natural and the pathological. Pest infestations in collections of organic materials are both natural and endemic, related to the ecosystem. Controlling their population size involves repeated actions and a specific follow-up treating simultaneously all contextual factors. This approach, which reduces the use of biocides, is part of a sustainable development policy.